041 Serial change in health related quality of life over 1 year following transcatheter aortic valve implantation: predictors of health outcomes. (16th May 2012) - Fairbairn, T A; Meads, D M; Mather, A N; Motwani, M; Pavitt, S; Plein, S; Blackman, D J; Greenwood, J P
Abstract : Introduction: Severe aortic stenosis (AS) reduces the length and quality of a patient's life. Transcatheter Aortic Valve Implantation (TAVI) is superior to standard medical therapy and non-inferior to Surgical Aortic Valve Replacement (SAVR) for 1-year mortality. HRQOL is an important outcome measure, for which there is limited evidence in TAVI populations. This study aimed to assess serial changes in patient health related quality of life (HRQOL) over time and identify predictors of patient benefit. Method: 102 (age 80±0.6 years, female 51%) attending for TAVI consented to participate. Two HRQOL questionnaires, the SF12v2 with physical and mental component summaries (PCS and MCS) and the EQ-5D (with Visual Analogue Scale; VAS) were completed at baseline, 30 days, 6 and 12 months. A SF-6D utility measure was calculated from the SF12 survey. Results: HRQOL significantly improved over 12 months (PCS, p=0.002; EQ-5D, p=0.02; VAS, p=0.01; SF-6D p=0.048). The greatest change occurred from baseline to 30 days (p<0.001) with further significant increases to 6 months (p<0.01). An insignificant decline occurred between 6 and 12 months (p>0.05), Abstract 041 table 1 . Female gender (p<0.05), age ≥80 years (p<0.05), previous MI (p<0.04), CKD (p<0.05), pulmonary hypertension (p=0.04) and lower operator experience (p<0.001) were independent predictors of a smaller improvement in HRQOL, Abstract 041 figure 1 . Conclusions: HRQOL significantly improves early following TAVI and is maintained out to 1 year. Patient and procedural predictors of health benefit at 1 year may help patients and physicians make a fully informed decision during the TAVI selection process.